PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS SCHOOLOGY PADA MATA KULIAH PSIKOLOGI KOMUNIKASI MATERI ANTARPERSONAL DAN INTERPERSONAL DI JURUSAN BK UNIMED - Nasrun Nasrun; Dody feliks Pandimun Ambarita; Nani Barorah Nasution (Universitas Islam Negeri Sumatera Utara Medan, 2026)
The development of information and communication technology has brought significant changes in the world of higher education, particularly in the use of online learning media. This study aims to develop Schoology-based learning media for the Communication Psychology course, covering interpersonal and intrapersonal communication in the Guidance and Counseling Department of Medan State University. The research method used is Research and Development (R&D) with the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects consisted of lecturers and students of the Guidance and Counseling Department. Data collection techniques used expert validation questionnaires, student response questionnaires, and learning outcome tests. The results of the study indicate that the developed Schoology-based learning media is categorized as very valid, practical, and effective. Thus, this media is suitable for use as a supporting tool for Communication Psychology learning in higher education..